Efficacy of cleaning and sanitation methods in reducing foodborne pathogens on common food contact surfaces in Cambodian fresh food markets - Hay, Vannith (Kansas State University, 2023)
Fresh food markets are common shopping destinations in many parts of the world, especially in low- and middle-income countries (LMICs). However, these markets are also known for being potential sources of microbial contamination. Foodborne pathogens such as Salmonella enterica (Salmonella) and Escherichia coli (E. coli) are the two most common bacteria associated with fresh produce and animal source foods (ASF). These pathogens can contaminate food at any stage of the food value chain, from farm to table. In LMICs, these pathogens are often found in food items sold in fresh food markets. In fresh food markets in Cambodia, natural food packaging materials such as banana leaves and bamboo baskets are commonly used as food contact surfaces to store, transport, and display food items. These materials are typical used following traditional practices with the lack of hygiene and sanitation measures. Without proper cleaning and sanitation, Salmonella and E. coli can attach and persist on these surfaces and cross-contaminate other food products, presenting health risk to both market vendors and consumers. Therefore, there is a need to understand how to effectively control both Salmonella and E. coli on food contact surfaces typically used in fresh food markets. The objectives of this study were as follows: 1). demonstrate the attachment of Salmonella and E. coli on banana leaf and bamboo basket surfaces; 2). evaluate the efficacy of cleaning and sanitation methods in reducing Salmonella and E. coli experimentally inoculated on banana leaf and bamboo basket surfaces; 3). suggest possible food safety interventions for fresh food markets in Cambodia. To determine the antimicrobial effectiveness of cleaning and sanitation methods in reducing Salmonella on banana leaf and bamboo basket surfaces, 15 different treatments combining cleaning and sanitation methods were tested. Each treatment was carried over for 3 or 5 min. The cleaning methods include wiping, scrubbing, and no cleaning (i.e., control), whereas the sanitation methods comprise of 200 ppm bleach, 400 ppm peracetic acid (PAA), and no sanitation (i.e., control). Banana leaf and bamboo basket surfaces were inoculated with an overnight culture of a Salmonella cocktail. Surfaces were then cleaned and sanitized in accordance with each defined treatment. Survival populations of Salmonella were neutralized and enumerated. Data suggested that PAA was the most effective sanitizer in reducing Salmonella (4.31 log CFU/cm² reduction, 95% confidence interval [CI; 4.14, 4.46]) on banana leaf surfaces regardless of cleaning method or contact time applied. Statistical analysis indicated a significant interaction between cleaning and sanitation method on banana leaf surfaces, suggesting that efficacy of sanitation was dependent on the cleaning method used. Wiping followed by bleach for 5 min significantly reduced Salmonella by 2.90 log CFU/cm² (95% CI [2.72, 3.09]) on banana leaf surfaces as compared to the control (i.e., no cleaning and no sanitation). On the other hand, there is no evidence of any significant interaction between cleaning and sanitation method in reducing Salmonella on bamboo baskets. The most effective treatment on bamboo baskets was the use of PAA for 5 min achieving a 2.26 log CFU/cm² reduction of Salmonella as compared to the control. A similar experimental design was followed to examine the effect of cleaning and sanitation method in reducing E. coli on banana leaf and bamboo basket surfaces. Data showed that a significant reduction of E. coli on bamboo baskets were dependent of both cleaning and sanitation applied, highlighting their interactions or combined effects. On bamboo baskets, the most effective treatment was the use of PAA for 5 min following no cleaning, reducing E. coli by 4.03 log CFU/cm² as compared to the control. On banana leaf surfaces, PAA reduced E. coli counts to below the limit of quantification (1.44 log CFU/cm²) reaching a 3.70 log CFU/cm² reduction regardless of the cleaning method or contact time examined. The results of this study highlight the importance of cleaning and sanitation practices in fresh food markets. The implementation of proper cleaning and sanitation for food contact surfaces is crucial in reducing the risk of contracting foodborne illnesses associated with the consumption of food originated from fresh food markets. Stakeholders may utilize this finding to select an appropriate food contact surface and develop effective cleaning and sanitation procedures that may contribute to ensuring the safety of consumer.
Keywords: Cleaning and sanitation; Food contact surfaces; Fresh food markets; Cambodia; Banana leaves; Bamboo baskets